Tannic acid and cholesterol–dopamine as building blocks in composite coatings for substrate‐mediated drug delivery. Issue 11 (8th April 2016) - Zhang, Yan; Baekgaard‐Laursen, Marie; Mouritzen, Sidsel A; Lynge, Martin E; Schattling, Philipp S; Danial, Maarten; Postma, Almar; Städler, Brigitte
Abstract : A comparison is made between polydopamine and tannic acid polymer films, with embedded paclitaxel‐loaded liposomes, for their ability to prevent hepatocyte adhesion. Abstract: Composite coatings are considered a promising approach to tailor the biointerface between a (implantable) biomaterial and adhering/surrounding cells or tissue. In this context, composite coatings assembled using a polymer matrix with embedded drug deposits are particularly interesting due to the advanced control over cargo loading, retention and release. Herein, we compare the assembly of such films consisting of various types of liposomes as subunits within a polymer film of either polydopamine (PDA) or, for the first time, tannic acid (TA) as an alternative. It is found that TA is a suitable capping layer for liposome‐coated substrates which allows for post‐modification. The composite coatings are suitable for supporting hepatocyte adhesion depending on the terminating polymer layer. Furthermore, incorporation of cholesterol–dopamine (Ch‐DA) conjugates into the zwitterionic liposomes increases the numbers of deposited subunits. Finally, cytotoxic paclitaxel is loaded into the liposomes and delivered to the adhering hepatocytes. The capability of reducing hepatocyte adhesion to the composite coating varied. Composite coatings consisting of negatively charged liposomes with Ch‐DA and a PDA capping layer are found to be most efficient after 24 and 48 h. Taken together, this fundamental comparison of different composite coatings illustrates the excellent opportunities to engineer the biological response towards the application in mind. © 2016 Society of Chemical Industry